Penyelesaian Sengketa Tanah Ulayat Masyarakat Hukum Adat Suku Ngalum dengan Pemerintah Daerah Kabupaten Pegunungan Bintang - Hadi, Supriyanto; Solossa, Marthinus; Rongalaha, Johan; Palenewen, James Yoseph (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the process of land acquisition of the customary law community of the Ngalum tribe for development by the Regional Government of Pegunungan Bintang Regency and to determine how to resolve customary land disputes of the customary law community of the Ngalum Tribe with the Regional Government of Pegunungan Bintang Regency. The methods used in this study are normative and empirical juridical, normative juridical is an approach that refers to laws, literature, written regulations or other secondary legal materials, while empirical juridical is identifying and conceptualizing law as a real and functional social institution in a real life system. The results of this study reveal that the process of land acquisition of the Ngalum Tribe with the Regional Government of Pegunungan Bintang Regency goes through several stages of the implementation process starting from planning, preparation, implementation and submission of results. Meanwhile, there are generally 2 (two) ways to resolve customary land disputes of the Ngalum Tribe, namely through the Iwol institution and the Aplim Apom Sibilki Customary Council.